Prioritizing Backyard Poultry Bottlenecks Using Analytic Hierarchy Process in Punjab, India - Chadda, Akshita; Singh, Jaswinder; Sharma, R K; Jadoun, Y S (Indian Journal of Extension Education, 2025)
Backyard poultry in rural India symbolizes both opportunity & adversity, offering livelihoods while battling chronic gaps in feed, healthcare & marketing. This study, conducted during 2022-2023, used the Analytic Hierarchy Process (AHP) to prioritize bottlenecks in the backyard poultry value chain. A total of 385 farmers from 11 districts of Punjab were purposively selected using the snowball sampling technique. The study revealed production constraints (priority weight: 0.250) as the leading challenge faced by respondents. Within input supply constraints, lack of access to credit and insurance support was ranked highest (global priority score: 0.109). High feed costs (0.065) and limited market information (0.037) were the most critical production and marketing challenges, respectively. Inadequate transportation (0.050) topped processing and transportation constraints. Predator attacks (0.079) were identified as the most alarming threat. The study highlights major bottlenecks requiring targeted interventions for sustainable rural poultry development.